Comparative transcriptome analysis of low- and high-latitude populations of Charybdis japonica under temperature stress - Sun, Shaolei; He, Zhiqi; Zhang, Feijun; Han, Zhiqiang (Frontiers in Marine Science, 2024)
Global climate change has caused rapid temperature changes in marine environments. Understanding how marine organisms respond to temperature changes can help predict their richness of future biodiversity. In this study, we examined the gene expression levels and the difference in the pathways that are responsive to acute temperature stress in low- and high-latitude populations of the shore swimming crab, Charybdis japonica. The two populations of C. japonica were exposed to low- and high-temperature stresses (15°C and 28°C) and used for transcriptome sequencing. Genetic regulatory ability changes were compared to determine the diverse response of the two crab populations to temperature change. The gene expression levels and functional enrichment analysis showed that the low-latitude crab regulated more genes (938) that were mainly enriched in DNA replication and metabolic pathways, whereas the high-latitude crab regulated less genes (309) that were mainly enriched in genetic information processing at low-temperature stress. Furthermore, the low-latitude crab regulated less genes (33) that were mainly enriched in genetic information processing, whereas the high-latitude crab regulated more genes (280) that were mainly enriched in signal transduction and cellular process at high-temperature stress. These results implied that the low-latitude population was more resilient to high-temperature stress, while the high-latitude population was more resilient to low-temperature stress. This study enhances our understanding of how different geographic C. japonica populations respond to varying temperature environments in their living zone, which could be helpful for predicting future biodiversity trends of intertidal crustaceans under global climate change.